2018
DOI: 10.1590/0102-311x00027917
|View full text |Cite
|
Sign up to set email alerts
|

An empirical assessment of the Healthy Early Childhood Program in Rio Grande do Sul State, Brazil

Abstract: We investigate the effect of a family-based primary health care program (Healthly Early Childhood Program) on infant mortality in the state of Rio Grande do Sul, Brazil. We estimate infant mortality's counterfactual trajectories using the differences-in-differences approach, combined with the use of longitudinal data for all municipalities in the state of Rio Grande do Sul. Our main result is that the program reduced the number of deaths caused by external causes. The length of exposure to the program seems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
7
1
Order By: Relevance
“…However, there are still no published evaluations of the effect of PIM or Criança Feliz on ECD in quasi-experimental longitudinal studies or RCTs. Previous ecological studies suggested the existence of associations between PIM and reduced child mortality from external causes 23 and reductions in school violence. 24 One cross-sectional study with a sample of 571 children found no differences in ECD between PIM intervention and control groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still no published evaluations of the effect of PIM or Criança Feliz on ECD in quasi-experimental longitudinal studies or RCTs. Previous ecological studies suggested the existence of associations between PIM and reduced child mortality from external causes 23 and reductions in school violence. 24 One cross-sectional study with a sample of 571 children found no differences in ECD between PIM intervention and control groups.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, findings from this evaluation strengthen PIM’s scientific evidence-base24 28 56 and empirically establish responsive caregiving as a key mechanism of change in the intervention’s logic model. They also build on the small body of parenting intervention research previously conducted in Brazil, which has been primarily limited to small-scale, researcher-designed interventions 57–59.…”
Section: Discussionmentioning
confidence: 52%
“…PIM became a public policy by law in 2006 and served as a model for Brazil’s federal parenting programme, Crianca Feliz (CF), which is the largest home-visiting programme in the world 27. Previous studies have found that children who received PIM demonstrated small reductions in infant mortality28 and school-reported behaviour problems29 and improvements in cognitive development 24. This is the first peer-reviewed evaluation of its kind to assess PIM’s effect on parent behavioural mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…While citing evaluations that describe how children from the programme attain superior achievement in practically all areas (cognitive development, language, motor function, socio-emotional behaviour, and so on), the author goes on to point out the gross shortcomings -whether in terms of project design, sample selection or statistical analysis -of literally every one of the studies (Verch, 2017). In another more recent statistical evaluation carried out by universitybased researchers of PIM, the authors clearly state that they have found no reliable evidence to demonstrate the programme's positive impact on children's cognitive or socioemotional performance (Ribeiro et al, 2018).…”
Section: Econometrics: From Mathematical Equations To Moral Injunctionsmentioning
confidence: 99%